Analysis of Factors Influencing the Marketing Information System: CRM, Customer Satisfactaction and Sales Effectiveness - Uci Rosalinda, Ursula; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2023)
Literature Review Article Analysis of Factors Affecting Marketing Information System: CRM, Customer Satisfaction and Sales Effectiveness is a scientific article that aims to build research hypotheses on the influence of variables to be used in further research, within the scope of ESSB. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are that: 1) CRM influences operational excellence and increases customer satisfaction through a cooperative relationship with the marketing information system. ; 2) Customer satisfaction affects the marketing information system; and 3) sales effectiveness affects the marketing information system. Apart from these 3 exogenous variables that influence the endogenous variables of the Finance Information System there are many other factors including the variables of Planning, Management and Internal Audit of the company.